TREATMENT PROFILES AND RISK FACTORS FOR CLINICAL OUTCOMES OF CONFIRMED COVID-19 AND PNEUMONIA PATIENTS AT FATMAWATI GENERAL HOSPITAL JAKARTA - HARAHAP, NOFRIA RIZKI AMALIA; ANDRAJATI, RETNOSARI; SUBHAN, AHMAD (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: This study aimed to investigate the treatment profiles and the risk factor for clinical outcomes of confirmed coronavirus disease-19 (COVID-19) and pneumonia patients at Fatmawati General Hospital Jakarta. Methods: This research was conducted using a cross-sectional design at Fatmawati General Hospital Jakarta. A total of 72 adults COVID-19 confirmed patients with pneumonia diagnosis from March to December 2020 were included in our study. Data were collected retrospectively by the patients’ medical record. Results: The percentage of critical or severe confirmed COVID-19 with pneumonia inpatients (66.7%) was higher than those who were having non-severe diseases (33.3%). 36 (50%) death were reported in our patient population. Patients received antiviral, antibiotics, and steroids during a treatment period. The most common antibiotic regimens were levofloxacin intravenous (IV) (18.8%) and azithromycin per oral (PO) (13.9%). Oseltamivir (83.3%) was the most frequently prescribed antiviral for the patients. A total of 41.7% of patients used steroids. In multivariable logistic regression analyses, the severity of COVID-19 disease was the only predictive factor of death in COVID-19 and pneumonia patients (p<0.001, OR=26.714, 95% confidence intervals: 5.526–129.135). Conclusion: Some drugs (antiviral, antibiotics, and steroids) have been prescribed to the confirmed COVID-19 with pneumonia patients. Oseltamivir and levofloxacin were the widely used antiviral and antibiotic agents in this study. The analysis showed that the disease severity was statistically associated with patient’s clinical outcomes. COVID-19 patients with the severe illness have a greater risk of death.